Challenges of Governance
XI, 274 p. 11 illus., 5 illus. in color.
Keywords: This book presents a varied and multi-dimensional view of challenges of governance in Southeast Asia and ASEAN through the variety of disciplines and nationalities involved. In light of 50 years of regional collaboration and integration as the member states of ASEAN seek to chart out a future path for the region, this book is dedicated to showcasing different challenges to governance that occur due to internal and external pressures for the various member states. The editors are particularly interested in the multi-level governance challenges on issues of democracy, equity, and sustainability, the adaptation of policies and norms to fit an ASEAN way, and the changing roles of civil society and citizens in this process of seeking a common identity and voice. The book is divided into four sections. The first section introduces the fundamental political institutional dynamics that are in play within the region and the interplay between regional forces and national norms. The secondsection tackles the economic and legal discourses that various member states face in relation to external and internal pressures related to international and regional trade and industry. The third section focuses on issues of sustainability and equity resulting from the vast socio-spatial differences in the varied cities and regions of member states. In the final section, the authors discuss dilemmas resulting from economic growth in exploitative industries and the impact that has on the local and regional community through the lenses of inclusivity and justice. Written by a diverse collection of policy makers, researchers, educators and activists from the regions discussed, this book provides an authoritative first-hand analysis of key challenges to governance in Southeast Asia and ASEAN. As such, this volume is an excellent resource for academics, advanced masters and PhD candidates interested in the region, and major Southeast Asian research institutes and centers as well as policymakers and influencers at both national and regional levels within the region.